The Economic Utilization and Processing of Poultry By-products in Butcher Shops in Kabul City - Sarwary, Nasir Ahmad; Zamani, Mohammad Najib (Journal of Natural Sciences – Kabul University, 2025)
This study explores the economic potential and utilization practices of poultry by-products in butcher shops across Kabul. The research aims to identify significant challenges, assess public health and economic issues, and propose practical strategies to improve processing efficiency and minimize waste. A total of 40 structured questionnaires were distributed among poultry butchers in various districts of Kabul. Three experts evaluated the validity of the questionnaire, and its reliability was confirmed using Cronbach’s alpha coefficient (0.79). The findings reveal that most poultry by-products are processed using basic, traditional methods, while others—such as blood and bones—are commonly discarded. The study highlights the importance of adopting appropriate technologies and infrastructure development to improve the utilization of these by-products. It concludes that better management could reduce waste and create new economic opportunities. The study recommends improving quality standards and regulatory monitoring to ensure the safe and efficient processing of poultry by-products.